Pragmatic Interpretation of the Learners’ Unique English Utterances in Kampung Inggris - Ubaidillah (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study concerned with the English conversation of the learners of second language in Kampung Inggris, Pare, Kediri, in which aimed to identify the unique English utterances, to describe the semantic meaning (literal meaning) and pragmatic interpretation (intended meaning) and to identify the structure of the learners’ unique English utterances. This study used qualitative research method by using two methods: participant observation and semi-structured interview. The result of this study showed that few unique English utterances uttered by the learners in Kampung Inggris whether in the form of phrases or sentences during conversation. These unique English utterances were uncommon and different from daily English utterances of native speaker. Moreover, the structures of their English were also different from the Standard English Rules. The ungrammatical structures of their utterances were found such as in the form of pronoun agreement, verb grouping, question formation, comparative degree, adjective order, word choice, addition to be and omission auxiliary. Thus, their English utterances were ambiguous during interaction. In conclusion, the unique English utterances of the learners in Kampung Inggris were caused by the tendency of the learners in simplifying English translated word by word without considering the target language of the context. Meanwhile, this tendency of simplification was influenced by inter-language interference and intra-lingual factor.